2018
DOI: 10.1109/tvt.2018.2849571
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Indoor Propagation Using FDTD Method With Spatial Averaging

Abstract: The error in the local mean magnitude of the electric field (E-field), due to the numerical anisotropy, obtained by the finite-difference time-domain (FDTD) method is investigated. The spatial averaging is applied over a cube. In order to quantify the error, the numerical results are compared with theoretical and measured ones. The comparison between the FDTD method and theory is conducted for two empty rooms with perfect electric conductor (PEC) walls at 3 and 5 GHz. It is found that averaging over a cube wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Otherwise, if the distance from a small cell in the LOS/NLOS region is smaller than R L/N , the signal is considered as a detectable signal. The summation of all interference signals are defined as I B , which is computed by (14).…”
Section: Computation Of Ig Assumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, if the distance from a small cell in the LOS/NLOS region is smaller than R L/N , the signal is considered as a detectable signal. The summation of all interference signals are defined as I B , which is computed by (14).…”
Section: Computation Of Ig Assumptionmentioning
confidence: 99%
“…Traditionally, research on indoor wireless networks performance has focused on indoor propagation channel modelling [9]- [14], random blockage modelling [15]- [17], and line-of-sight (LOS) probability analysis [18]- [21], etc. Analysis on indoor network performances has therefore shed light on the impact of building structures on specific wireless networks performance.…”
mentioning
confidence: 99%
“…In [25] the authors conducted simulations of the estimation of the electric field strength at 3 GHz and 5 GHz, using the FDTD method It was found that averaging over a 3D volume, a cube with a side length of 3.3λ, showed agreement between the local mean magnitude of the simulation and the theoretical electric field. Measurements and simulation were conducted at 3 GHz and it was found that as the averaging volume increased the error of estimating the electric field decreased.…”
Section: Previous Related Workmentioning
confidence: 99%
“…The FDTD is a full‐wave method for the spatial and temporal discretization of the differential Maxwell's equations 7 . Due to its wide applicability and simple programming, it has been applied to both narrowband and wideband indoor channel analysis 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…7 Due to its wide applicability and simple programming, it has been applied to both narrowband and wideband indoor channel analysis. [8][9][10] The FDTD grid is based on Cartesian coordinate system, so there will be a large error due to the staircase approximation when dealing with curved objects. In order to reduce the staircase error, several hybrid subgridding techniques have been proposed in reference 11-13, but it is difficult to eliminate the reflection between cell boundaries by using these methods.…”
Section: Introductionmentioning
confidence: 99%